Illness as intersubjectivity: a sociological perspective - Pitfield, Doreen Jennie (Rhodes University, Faculty of Humanities, Department of Sociology, 1992)
This thesis explores the historical roots of scientific medicine in an effort to highlight the lack of humanist intersubjectivity within the contemporary medical model. The study notes that contemporary medicine is overtly scientific and that its scientific framework is upheld and furthered by a medical model which draws legitimation from the irrefutability of what is referred to variously within this work, as its scientific "regime". It is shown that in terms of the humanist tradition people, not science, constitute the epicentre of meaningful experiential participation in the defining of human social reality. This, it is argued, implies a radically different ontology from other sociological perspectives on medicine. The thesis suggests that the contemporary medical model loses sight of the patient's ability to cognitively participate in the defining of illness, diagnosis and treatment in terms of his/her experience thereof , and argues that contemporary medicine, by advancing the idea that it alone has the correct and only answer to such problems, has led to a situation which promotes an overmedicalisation of society . The study gives an indication of the way in which this overmedicalisation has led to areas of human life becoming conceived of only in relation to medical expertise. In this respect it is noted that medicine has so successfully infiltrated the human consciousness (involving areas as diverse as childbirth, genetic engineering, transplant surgery and death), that decisions on health are invariably taken from a foundation of scientific legitimation which seems to exclude the patient as subject. It is argued that this way of making decisions reinforces the requirement for a scientific medical model which as it negates the human element insidiously amplifies its power over human life; thereby devaluing the very people it seeks to serve. The thesis suggests that in terms of a humanist reading of the Oath of Hippocrates, medical decisions can only be taken within a framework of experiential involvement which includes both medical expertise and lay understanding. It is indicated that when this happens, social reality functions in terms of a symbolic participation which fosters a commitment to equalise the conditions of human existence, and promotes a dialogical negotiatory process which is both intersubjectively and ongoingly produced.
Keywords: Humanism; Medical care -- Sociological aspects; Intersubjectivity; Medical ethics -- Sociological aspects